Cerebrospinal Fluid Interaction with Cerebral Cortex during Pediatric Abusive Head Trauma - Toma, Milan; Dehesa-Baeza, Alfonso; Chan-Akaley, Rosalyn; Nguyen, Paul D. H.; Zwibel, Hallie (Journal of Pediatric Neurology, 2020)
Abusive head trauma is the leading cause of fatal brain injuries in children younger than 2 years. It is a preventable and severe form of physical child abuse often linked to the forceful shaking of an infant or toddler. Victims of abusive head trauma can suffer permanent neurological damage, resulting in developmental delay and disability. The long-term effects of abusive head trauma are difficult to diagnose and predict. In this model, we use a high-order finite element method paired with the most comprehensive and current head/brain model and next-generation smoothed particle hydrodynamics. This is one of the first fluid–structure interaction frameworks that uses fluid material properties to represent the cerebrospinal fluid (CSF) while including all major anatomical features of the brain. The interaction of CSF with the brain cortex during abusive head trauma is demonstrated during multiple shaking cycles. A comprehensive and precise model that calculates for the role of CSF in neurological trauma will be useful both in the prevention and treatment of abusive head trauma and the determination of prognosis and patient outcomes.
Keywords: fluid–structure interaction; cerebrospinal fluid; comprehensive head; model; brain; coup; contrecoup; injury; trauma